Bacterial membrane disruption in food pathogens by Psidium guajava leaf extracts - Francis Parillon, Henie Edward; Hassan, Zaiton; Mohamed, Suhaila (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2009)

(untitled)
The mode of action and activities of guava leaf extracts against various food pathogens were studied. The killing kinetics, viability and cell leakage of Kocuria rhizophila, Salmonella typhimurium, Listeria monocytogenes and Escherichia coli O157:H7, measured after exposure to guava methanolic extracts (GME) revealed a significantly higher (p≤0.05) release of bacterial nucleic acids, K + ions and protein than that of untreated microbes, indicating disruption of the bacterial membrane. GME caused a significantly higher (p≤0.05) release of RNA in gram-negatives compared to gram-positives. GME caused a relatively small but significant release of pyrines and pyrimidines in all organisms investigated. GME probably disrupted the integrity of the Gram-negative microorganism lipopolysaccharide (LPS) layer. Unlike all the other microorganisms tested, E. coli O157:H7, demonstrated the lowest protein leakage, the highest K+ leakage, the highest pyrines and pyrimidines leakage within the first 10 min of extract exposure, but the lowest after 30 minutes, which may indicate their good homeostasis ability or adaptability. Understanding the mode of action of this flavonoid rich guava leaf extract, would help develop it as an alternative biodegradable and safe, antimicrobial for food and medicine, and as a by-product of the guava industry.